The Effect Of Third-Party Funds (Dpk), Capital Adequacy Ratio (Car), Return On Assets (Roa), And Return On Equity (Roe) On Financing In Btpn Syariah - Mohammad Irvan Setiawan; Renny Oktafia (International Journal of Economics, Business and Innovation Research, 2024)
The banking industry plays an important role in a country's economy, functioning as an intermediary institution and managing risks associated with financing. This study aims to evaluate the influence of Third Party Funds (DPK), Capital Adequacy Ratio (CAR), Return On Assets (ROA), and Return On Equity (ROE) on financing in BTPN Syariah. The data used is a quarterly time series data for 10 years, from the fourth quarter of 2014 to the fourth quarter of 2023, following the availability of data on the BTPN Syariah website after becoming a Sharia Commercial Bank (BUS) in July 2014. This study uses the Error Correction Model (ECM) to handle non-stationary data and prevent regression, as well as multiple linear analysis with the Ordinary Least Squares (OLS) method to test the influence of variables. The results of the study showed that deposits had a positive and significant effect on financing, CAR had a positive but not significant effect. ROA also had a positive but not significant effect. ROE has a negative and insignificant effect on financing.